Meningkatkan Kemampuan Menyimak Peserta Didik Melalui Layanan Bimbingan Konseling Belajar Berbasis Gaya Belajar Di Kelas VIII SMP Negeri 3 Dolok Masihul - Gustina Suryani (Pusat Riset dan Inovasi Nasional, 2024)
Students' success in completing education can be seen from their learning achievement, so learning achievement is a benchmark for educational outcomes in school. Considering that learning achievement is one measure of a student's learning success, the ability to listen itself has a big influence on learning achievement. In this regard, here the researcher wants to implement learning counseling services based on students' learning styles to overcome the problem of students' listening abilities. This Guidance and Counseling Action Research was conducted at SMP Negeri 3 Dolok Masihul. The time and activities of this research are from September to November 2022. This research approach uses a quantitative qualitative approach. The population of this research is all students in class VIII of SMP Negeri 3 Dolok Masihul for the 2021/2022 academic year, while the sample for this research is students from class VIII only, that is, only 24 students were taken. This research instrument includes: observation sheet, interview guide and documentation. In the initial conditions, researchers had not implemented learning counseling services based on students' learning styles. In the pre-cycle, researchers looked for data on student learning scores in 1 subject area. The results of the pre-cycle research were 8 students who got a score of 50-74, and 16 students who got a score of 75-100. The results of the first cycle of research can be seen that students whose grades were completed (KKM=75) had increased, namely 17 students (70.83%), while those who did not complete were 7 students (29.16%). The results of the second cycle of research of students whose grades were completed (KKM=75) had increased, namely 24 students (100%), while those who did not complete were 0 students (0%). The final result of this research is that learning counseling services based on student learning styles can improve the learning achievement of class VIII students at SMP Negeri 3 Dolok Masihul.